Reducing switching losses of resonant inverter - Roy, Pinak; Hossain, Md. Shafayat; Shahriar, Saklayan (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.